Turning Points in Jewish History - Rosenstein, Marc, 1946- (Book collections on Project MUSE., 2018)
"Examining the entire span of Jewish history through the lens of thirty pivotal moments in the Jewish people's experience from biblical times through the present, Turning Points in Jewish History provides "the big picture": both a broad and a deep understanding of the Jewish historical experience"--